Effects of sonication on particle dispersions from a size, biodissolution, cytotoxicity and transferred dose perspective – a case study on nickel and nickel oxide particles - Eva Blomberg; Xuying Wang; Gunilla Herting; Alexander Khort; Abishek Arora; Samuel Buxton; Tara Lyons-Darden; Hanna L. Karlsson; Inger Odnevall (PLoS ONE, 2025)
The toxicity of micro- and nanoparticles in cell culture studies is influenced by factors like particle size, agglomeration, dissolution of the particles, and methodological factors like sonication protocols. The main aim of this study was to investigate the influence of sonication on the particle size, dissolution, cytotoxicity, and dosing accuracy of nickel (Ni) metal and Ni oxide (NiO) particle dispersions. Such investigations are important to enable studies on the cellular uptake of different Ni substances in lung cells. The effect of sonication was evaluated in ultrapure water, two types of cell media, and A549 human lung cells using the tip and water bath methods. Extended sonication significantly decreased particle size and increased particle dissolution, emphasizing the need for optimized sonication conditions tailored to the specific particle type and study design. Observed findings demonstrate that the sonication step potentially can have a large impact on the results due to changes in particle characteristics, size, and dissolution, properties which are highly dependent on the particle type, solution composition, and sonication parameters. Although only small differences were observed in the limited assessment of cytotoxicity (A549 cells) in this study, further investigation is required to determine the impact of sonication on toxicity. This study also emphasizes the need to evaluate transferred dose samples due to the evident effects of agglomeration, sedimentation, and losses during sample transfer of particle dispersions. The study clearly illustrates that the choice of sonication protocol is particularly critical for toxicity studies, which are the basis of government regulatory decisions and human exposure limits.